A Comprehensive Review on the Endemic Plant Docynia indica: Its Ethnobotanical, Phytochemical, and Ethnomedicinal Perspective - Biswas, Joy; Barman, Pranjan; Rahman, Mehzabin; Ghosh, Rajgourab (Asian Journal of Biological and Life Sciences)
Ethnobotanical knowledge and ethnomedicinal methodologies from different parts of the world are of comprehensive significance and documentation of ethnobotanical, and ethnomedicinal data is a key prerequisite for further research in the domain of herbal medicine and its implementation in modern clinical research. The important sources of beneficial natural products and ethnomedicinal elements are majorly contributed by the wild edible fruits. The Docynia indica is a wild edible fruit that belongs to the Rosaceae family and mainly disseminates in the eastern region of the Himalayas. Since immemorial time Docynia indica is an integral part of ethnomedicine and traditionally implemented for treating innumerable health diseases. It is a valuable ethnomedicinal plant with important sources of minerals and vitamins and is conventionally used for treating common ailments. In the traditional system of medicine, it is regarded as a wonderful prophylactic for combating enteric diseases. The natural compounds extracted from the fruits of Docynia indica contain polyphenol especially alkaloids and flavonoids which significantly have an antihyperglycemic and anti-hyperlipidemic property. The wild edible fruits are underemphasized despite their fascinating ethnobotanical and ethnomedicinal characteristics. Similarly, Docynia indica is a less explored endemic fruit that contains eminent natural compounds and ethnomedicinal importance. Though it is less popular in urban regions but in ethnic groups it is a key component in indigenous traditional medicine system. This article mainly discusses the morphological features and phytochemical constitutes of Docynia indica and ethnobotanical characteristics highlighting the ethnomedicinal perspective.
Keywords: Docynia indica; Endemic Fruits; Ethnobotany; ethnomedicine; Wild apple; Wild edible fruit.